SPK: ANALISIS METODE VIKOR DALAM MEREKOMENDASIKAN KOSMETIK TERBAIK DI KALANGAN MASYARAKAT - Ninaria Purba; Kiki Apni Puspita Sari; Alrizca Trydillah M; Agus Perdana Windarto (Jurnal Informatika, 2018)
Lipstick is a makeup or cosmetic tool that has many benefits other than as a lip color, lipstick also has a function as a moisturizer on the lips. Lipstick has many types from solid to liquid. The purpose of this study was to recommend the best lipstick cosmetics based on community assessment. This research method using the method of vikor. The criteria used are information about product (A), price, health (C), safety (D), manufacturing process (E), halal label (F), and buyer decision (G). Alternative cosmetics used: Data collection was done by survey/questionnaire to 20 respondents. The result of research is that Wardah has value 3,979198, Purbasari have value 3,183502, Pixy has value 1,915467, Sariayu martatilaar with value 3,226965, Mirabela with value 2,536226. Thus the greatest value of the five alternatives is Wardah with a value of 3.979198.